2000
DOI: 10.14214/sf.640
|View full text |Cite
|
Sign up to set email alerts
|

A process-based growth model for the grass stage pine seedlings

Abstract: A carbon-and nitrogen-balance model, applying pipe model theory and a modification of functional balance as growth-guiding rules, is presented for the grass stage pine seedlings. Three populations of Pinus merkusii Jungh. et de Vriese, originating from northern and northeastern Thailand, were grown under controlled environment for 47 weeks to obtain parameter information, to evaluate the model performance and to investigate genotypic variation in various characteristics among the populations. Monte Carlo simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…In fact, large trees can tolerate sustained drought periods extending over the entire growing season and even across multiple growing seasons , while such severe drought periods can lead to mortality of seedlings and saplings (for seedling physiological responses see Mendel et al, 1997;Mueller et al, 2005;Lopez and Kursar, 2007). The presence of large carbon reserves in mature plants can also allow for new shoot formation and resprouting (in resprouting species) following catastrophic events such as fire (Koskela, 2000;Langley et al, 2002) and breakage of branches or entire stem (Génard et al, 1998;Verdaguer and Ojeda, 2002;van Bloem et al, 2003;Wong et al, 2005;Vargas, 2009;Vargas et al, 2009). Thus, the availability of large reserves contributes to survival of and greater recovery after such devastating events.…”
Section: Effects Of Ontogeny On Stress Sensitivitymentioning
confidence: 99%
“…In fact, large trees can tolerate sustained drought periods extending over the entire growing season and even across multiple growing seasons , while such severe drought periods can lead to mortality of seedlings and saplings (for seedling physiological responses see Mendel et al, 1997;Mueller et al, 2005;Lopez and Kursar, 2007). The presence of large carbon reserves in mature plants can also allow for new shoot formation and resprouting (in resprouting species) following catastrophic events such as fire (Koskela, 2000;Langley et al, 2002) and breakage of branches or entire stem (Génard et al, 1998;Verdaguer and Ojeda, 2002;van Bloem et al, 2003;Wong et al, 2005;Vargas, 2009;Vargas et al, 2009). Thus, the availability of large reserves contributes to survival of and greater recovery after such devastating events.…”
Section: Effects Of Ontogeny On Stress Sensitivitymentioning
confidence: 99%
“…An earlier developed carbon-and nitrogen-balance model for the grass stage pine seedlings (Koskela 2000a), applying pipe model theory and a modi®cation of functional balance as growth-guiding rules, was used for simulations of growth. The model is based on material¯ows between a tree and its environment, and within a tree (e.g.…”
Section: Modelling Biomass Growthmentioning
confidence: 99%
“…The growth model explained reasonably well the variation in biomass and height growth of the grass stage seedlings under present climate (Figs 6 and 7). The model performance has earlier been analysed in a growth chamber experiment (Koskela 2000a) in which it was found that a linear relationship between height and needle mass may not yield a satisfactory ®t to measured height development. Therefore, this relationship was modelled in the present study using the exponential growth function, which seem to link height and needle mass development better than the linear relationship during the grass stage.…”
Section: Measured and Simulated Growthmentioning
confidence: 99%
See 2 more Smart Citations